2013
DOI: 10.1186/scrt387
|View full text |Cite
|
Sign up to set email alerts
|

Enteric nervous system abnormalities are present in human necrotizing enterocolitis: potential neurotransplantation therapy

Abstract: IntroductionIntestinal dysmotility following human necrotizing enterocolitis suggests that the enteric nervous system is injured during the disease. We examined human intestinal specimens to characterize the enteric nervous system injury that occurs in necrotizing enterocolitis, and then used an animal model of experimental necrotizing enterocolitis to determine whether transplantation of neural stem cells can protect the enteric nervous system from injury.MethodsHuman intestinal specimens resected from patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
78
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(87 citation statements)
references
References 42 publications
6
78
0
Order By: Relevance
“…The clinical pathological intestinal characteristics of an hypoxic-ischemic neonate may that disruption of these cells altered the neurochemical phenotype of enteric neurons, reduced transmission to muscle and delayed gastrointestinal transit (65,66). In this study, global HI-induced distortion of enteric glial cells in the ganglia of the myenteric plexus in a similar pattern found in animal models of HI-induced intestinal injury (67) and in neonates with NEC (31). Importantly, distortion of enteric glial cells upon gut HI has been correlated with loss of enteric neurons and impaired neuronal function, with subsequent decreased gastrointestinal motility (18,44,67,68).…”
Section: Resultssupporting
confidence: 55%
See 2 more Smart Citations
“…The clinical pathological intestinal characteristics of an hypoxic-ischemic neonate may that disruption of these cells altered the neurochemical phenotype of enteric neurons, reduced transmission to muscle and delayed gastrointestinal transit (65,66). In this study, global HI-induced distortion of enteric glial cells in the ganglia of the myenteric plexus in a similar pattern found in animal models of HI-induced intestinal injury (67) and in neonates with NEC (31). Importantly, distortion of enteric glial cells upon gut HI has been correlated with loss of enteric neurons and impaired neuronal function, with subsequent decreased gastrointestinal motility (18,44,67,68).…”
Section: Resultssupporting
confidence: 55%
“…In this study, we showed that global HI in fetal sheep induced intestinal inflammation, muscle thickening, distortion of enteric glial cells and altered neurotransmission. Although we can only speculate about the postnatal consequences of these adverse intestinal outcomes, the detected gut inflammation and ENS abnormalities following HI have been associated with neonatal gastrointestinal complications including loss of barrier integrity, delayed gastrointestinal motility and NEC (31,73,84). Future studies are warranted to investigate whether the detected pathological changes 7 d after UCO will have long-term adverse intestinal effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We hypothesized, that hepatocyte growth factor (HGF) and its receptor MET might also be important because HGF supports spinal motor neurons (Ebens et al, 1996), dorsal root ganglion (DRG) subtypes (Maina et al, 1997), retinal ganglion cells (Tönges et al, 2011), and hippocampal neurons (Lim and Walikonis, 2008). Our prior studies also suggested HGF expression in the ENS (Vohra et al, 2006). Finally, we were intrigued by the protective effect of HGF in rodent colitis models (Tahara et al, 2003;Mukoyama et al, 2005;Numata et al, 2005;Oh et al, 2005;Hanawa et al, 2006;Kanbe et al, 2006), and hypothesized that this might be mediated through MET-expressing enteric neurons.…”
Section: Introductionmentioning
confidence: 93%
“…Whole-mount myenteric plexus analysis was performed using 8 -12-week-old mice (n ϭ 3-6) as described previously (Wang et al, 2010). Briefly, gut was opened along the mesenteric border, pinned to Sylgard, fixed [4% paraformaldehyde (PFA), 30 min, 25°C], and then dissected to separate muscle layers from submucosa.…”
Section: Animals C-metmentioning
confidence: 99%